2015
DOI: 10.1002/14651858.cd003343.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Directly observed therapy for treating tuberculosis

Abstract: Background Tuberculosis (TB) requires at least six months of treatment. If treatment is incomplete, patients may not be cured and drug resistance may develop. Directly Observed Therapy (DOT) is a specific strategy, endorsed by the World Health Organization, to improve adherence by requiring health workers, community volunteers or family members to observe and record patients taking each dose. Objectives To evaluate DOT compared to self‐administered therapy in people on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
212
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 384 publications
(252 citation statements)
references
References 51 publications
13
212
0
8
Order By: Relevance
“…These meta-analyses are summarised in table 2. [186][187][188] The three meta-analyses were concordant in showing that supervised therapy was effective in reducing non-adherence and improving treatment completion. The meta-analyses also showed that no benefits were associated with DOTS compared with self-administered therapy when microbiological failure and relapse were examined as clinical endpoints.…”
Section: The Rise Of Drug-resistant Tuberculosis Historical Notions Omentioning
confidence: 93%
See 4 more Smart Citations
“…These meta-analyses are summarised in table 2. [186][187][188] The three meta-analyses were concordant in showing that supervised therapy was effective in reducing non-adherence and improving treatment completion. The meta-analyses also showed that no benefits were associated with DOTS compared with self-administered therapy when microbiological failure and relapse were examined as clinical endpoints.…”
Section: The Rise Of Drug-resistant Tuberculosis Historical Notions Omentioning
confidence: 93%
“…187 The incidence of acquired drug resistance was the same whether supervised therapy was given at home, in a health facility, by a family member, or by a community health-care provider. 186 None of these analyses identified single study effect or bias. Despite this apparent absence of an effect, the DOTS programme is useful because it is an example of political commitment by governments and ensures the continuous supply of good-quality drugs, which directly affects pharmacokinetic variability.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations